Chaplains in early modern England : patronage, literature and religion - Wright, Gillian, 1969-; Lockwood, Tom, 1975-; Adlington, Hugh (Politics, culture, and society in early modern Britain., 2013)
Who were early modern chaplains and what did they do? Chaplains are well known to have been pivotal figures within early modern England, their activities ranging from more conventionally religious roles (conducting church services, offering spiritual advice and instruction) to a surprisingly wide array of literary functions (writing poetry, or acting as scribes and editors). Chaplains in early modern England: Patronage, literature and religion explores the important, but often neglected, contributions made by chaplains of different kinds - royal, episcopal, noble, gentry, diplomatic - to early.